Utilization of genomic sequencing for population screening of immunodeficiencies in the newborn - Pavey, Ashleigh R; Bodian, Dale L; Vilboux, Thierry; Khromykh, Alina; Hauser, Natalie S; Huddleston, Kathi; Klein, Elisabeth; Black, Aaron; Kane, Megan S; Iyer, Ramaswamy K; Niederhuber, John E; Solomon, Benjamin D (Genetics in medicine, 2017)
Purpose Immunodeficiency screening has been added to many state-directed newborn screening programs. The current methodology is limited to screening for severe T-cell lymphopenia disorders. We evaluated the potential of genomic sequencing to augment current newborn screening for immunodeficiency, including identification of non–T cell disorders. Methods We analyzed whole-genome sequencing (WGS) and clinical data from a cohort of 1,349 newborn–parent trios by genotype-first and phenotype-first approaches. For the genotype-first approach, we analyzed predicted protein-impacting variants in 329 immunodeficiency-related genes in the WGS data. As a phenotype-first approach, electronic health records were used to identify children with clinical features suggestive of immunodeficiency. Genomes of these children and their parents were analyzed using a separate pipeline for identification of candidate pathogenic variants for rare Mendelian disorders. Results WGS provides adequate coverage for most known immunodeficiency-related genes. 13,476 distinct variants and 8,502 distinct predicted protein-impacting variants were identified in this cohort; five individuals carried potentially pathogenic variants requiring expert clinical correlation. One clinically asymptomatic individual was found genomically to have complement component 9 deficiency. Of the symptomatic children, one was molecularly identified as having an immunodeficiency condition and two were found to have other molecular diagnoses. Conclusion Neonatal genomic sequencing can potentially augment newborn screening for immunodeficiency.